Schisandrol A Exhibits Estrogenic Activity via Estrogen Receptor α-Dependent Signaling Pathway in Estrogen Receptor-Positive Breast Cancer Cells - Dahae Lee; Young-Mi Kim; Young-Won Chin; Ki Sung Kang (MDPI AG, 2021)
The aim of this study was to examine the estrogen-like effects of gentiopicroside, macelignan, γ-mangostin, and three lignans (schisandrol A, schisandrol B, and schisandrin C), and their possible mechanism of action. Their effects on the proliferation of the estrogen receptor (ER)-positive breast cancer cell line (MCF-7) were evaluated using Ez-Cytox reagents. The expression of extracellular signal-regulated kinase (ERK), phosphatidylinositol 3-kinase (PI3K), AKT, and estrogen receptor α (ERα) was measured by performing Western blot analysis. 17β-estradiol (E2), also known as estradiol, is an estrogen steroid and was used as a positive control. ICI 182,780 (ICI), an ER antagonist, was used to block the ER function. Our results showed that, except for gentiopicroside, all the compounds promoted proliferation of MCF-7 cells, with schisandrol A being the most effective; this effect was better than that of E2 and was mitigated by ICI. Consistently, the expression of ERK, PI3K, AKT, and ERα increased following treatment with schisandrol A; this effect was slightly better than that of E2 and was mitigated by ICI. Taken together, the ERα induction via the PI3K/AKT and ERK signaling pathways may be a potential mechanism underlying the estrogen-like effects of schisandrol A. This study provides an experimental basis for the application of schisandrol A as a phytoestrogen for the prevention of menopausal symptoms.